2015
DOI: 10.1002/eat.22411
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of treatment outcome in individuals with eating disorders: A systematic review and meta‐analysis

Abstract: To ensure that this area continues to develop with robust and clinically relevant findings, future studies should adopt a consistent definition of outcome and continue to examine complex multivariate predictor models. Growth in this area will allow for stronger conclusions to be drawn about the prediction of outcome for specific diagnoses and treatment types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
409
7
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(488 citation statements)
references
References 164 publications
41
409
7
10
Order By: Relevance
“…Given that depression and anxiety are related to poorer prognosis in EDs (Vall & Wade, 2015), these domains may be relevant validators of ED severity. In addition, quality of life and physical health convey clinical significance and may be expected to correspond with ED severity (Agh et al, 2016; Winkler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given that depression and anxiety are related to poorer prognosis in EDs (Vall & Wade, 2015), these domains may be relevant validators of ED severity. In addition, quality of life and physical health convey clinical significance and may be expected to correspond with ED severity (Agh et al, 2016; Winkler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis indicated that depression and general psychopathology unfavorably affected treatment outcome; however, the studies typically assess depression or anxiety with continuous measures such as the Beck Depression Inventory or State Anxiety Questionnaire score and do not necessarily stratify by diagnosis [190]. This is a potential problem, as one would, for instance, in a clinical setting prescribe an anti-anxiety or antidepressant medication based on a diagnostic assessment.…”
Section: New Approaches To Medication Intervention In Anmentioning
confidence: 99%
“…Como hemos visto en el apartado anterior, se han realizado grandes avances en la evaluación de los tratamientos en los TCA, sin embargo, son menos conocidos los predictores y moderadores de la respuesta al tratamiento (Agras et al, 2014;Iacovino et al, 2012: Le Grange et al, 2014Le Grange et al, 2012;Le Grange et al, 2008;Steinhausen and Weber, 2009;Thompson-Brenner et al, 2013;Vall and Wade, 2015).…”
Section: Predictores Moderadores Y Mediadores En Los Tratamientos Paunclassified
“…A pesar de estas dificultades, existen ya algunas investigaciones que se han centrado en estudiar los predictores que median en el resultado de los TCA (Agencia de Investigación y Calidad de la Salud, 2015; Berkman, Lohr y Shapiro et al, 2007;Vall y Wade, 2015).…”
Section: Predictores Moderadores Y Mediadores En Los Tratamientos Paunclassified
See 1 more Smart Citation